Technology teachers' talk about knowledge: from uncertainty to technology education competence - Nordlöf, Charlotta; Höst, Gunnar; Hallström, Jonas (Research in science & technological education, 2024)
The subject of technology looks different depending on context. There is also an epistemological complexity to technological knowledge in technology education. To gain a deeper understanding of the epistemological foundations of the subject of technology and technology teaching, the teachers' views are needed. The aim of this study is to examine how teachers discuss technology education, with a particular focus on how they talk about technological knowledge. 19 Technology teachers from compulsory school in Sweden participated. Through focus groups, teachers' views of knowledge in technology education were collected and then analysed. The results consist of three parts. Firstly, it was found that the teachers were unfamiliar with discussing epistemology in technology education. Secondly, interpreting their views of knowledge in technology education through a theoretical framework for knowledge in technology education yielded examples of knowledge from the three constituent categories: technical skills, technological scientific knowledge, and socio-ethical technical understanding. Finally, an inductive analysis revealed two categories based on the teachers' broader views of knowledge: civic capabilities and engineering capabilities. Overall, the results provide an understanding of teachers' ways of describing technological knowledge. The teachers perceived the term knowledge in a broader way than traditional epistemology, including capabilities in their descriptions. We propose a new perspective on the character of knowledge and capability in technology education, called technology education competence. The results of this study point to important aspects of the nature of the subject, which might lead to reflection about what knowledge should be considered of value in the future regarding research but especially development of curricula.